Dampak Independensi, Struktur Audit Dan Konflik Peran Terhadap Kinerja Auditor - Askolani Al Sayuti; Annisa Annisa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence of the effect of independence, audit structure and role conflict on auditor performance. The location of this research is in the Inspectorate Office of West Sumatra Province. The sample of this research was 30 respondents, all employees of the Inspectorate of West Sumatra Province and the method used was the total sampling method. The data collection method in this study uses a questionnaire method. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of multiple linear regression analysis shows that Independence has a positive effect on Auditor Performance, Audit Structure has no effect on Auditor Performance, Role Conflict has no effect on Auditor Performance.